Physical Multimorbidity and Social Participation in Adult Aged 65 Years and Older From Six Low- and Middle-Income Countries. (30th March 2021) - Ma, Ruimin; Romano, Eugenia; Vancampfort, Davy; Firth, Joseph; Stubbs, Brendon; Koyanagi, Ai
Abstract: Objectives: Multimorbidity is common among older adults from low- and middle-income countries (LMICs). Social participation has a role in protecting against negative health consequences, yet its association with multimorbidity is unclear, particularly in LMICs. Thus, this study investigated the relationship between physical multimorbidity and social participation among older adults across 6 LMICs. Method: Cross-sectional, community-based data including adults aged 65 years and older from 6 LMICs were analyzed from the WHO Study on Global AGEing and adult health survey. The association between 11 individual chronic conditions or the number of chronic conditions (independent variable) and social participation (range 0–10 with higher scores indicating greater social participation; dependent variable) was assessed by multivariable linear regression analysis. Results: 14, 585 individuals (mean age 72.6 [ SD 11.5] years; 54.9% females) were included. Among individual conditions, hearing problems, visual impairment, and stroke were significantly associated with lower levels of social participation. Overall, an increasing number of chronic conditions was dose-dependently associated with lower levels of social participation (e.g., ≥4 vs 0 conditions: β = −0.26 [95% CI = −0.39, −0.13]). The association was more pronounced among males than females. Discussion: Older people with multimorbidity had lower levels of social participation in LMICs. Future longitudinal studies are warranted to further investigate temporal associations, and whether addressing social participation can lead to better health outcomes among older people with multimorbidity in LMICs.